Syekh Arsyad Albanjari: Islamic Education Concept - Rahmat, Andi (Universitas Muhammadiyah Makassar, 2024)
The background to this research is that instilling the concept of Sheikh Aryad Albanjari's thoughts into students in schools through the subject of Islamic Religious Education, there is still a personality crisis in its implementation and a lack of material on the history of Banjar ulama which is included in PAI learning in schools. Meanwhile, Islamic religious education as a subject in Indonesia has an important role in raising awareness and increasing the quality and values of the Islamic religion among students, because the subject content contains religious values, morals and ethics.This research has a problem formulation of what are the values of Islamic religious education in the thoughts of Sheikh Muhammad Arsyad al-Banjari, how are Sheikh Muhammad Arsyad al-Banjari's efforts to instill the values of Islamic religious education, and what is the relevance of the values of Islamic religious education in the thoughts of Sheikh Muhammad Arsyad al-Banjari towards Islamic religious education in Indonesia. Answering this formulation by using factual historical research on figures by using the thoughts of figures from several works and the life history of Sheikh Muhammad Arsyad al-Banjari as research objectsThis research uses a philosophical approach which aims to find out, understand and explain the values of Islamic religious education and efforts to instill these values and find their relevance to Islamic religious education in Indonesia. After conducting studies, observations, research and analysis of severalthe works of Sheikh Muhammad Arsyad al-Banjari, namely the treatise Tuḥfaturragibīn, the book SabīlalMuhtadīn, Luqthatal 'Ajlān and Parukunan as well as the life history of Sheikh Muhammad Arsyad alBanjari. That the values of Islamic religious education in Arsyad's thinking are: 1) the goal of Islamic religious education is the goal of education in the world of the hereafter and social improvement, 2) the curriculum for Islamic religious education is the Koran, Hadiṡ, Fiqh, Tauhid, Akhlak, Arabic , Date 3) educators and students in Islamic religious education are educators who have knowledge and master it well and correctly, become role models, improve society both in terms of science and life, master learning methods, and who motivate students is someone who wants to and able to accept lessons within himself, which are in the process of growth and development which require knowledge guidance. The values within the scope of Islamic religious education are: 1) the value of aqidah education which contains the pillars of faith and strengthening faith in good and bad destiny by not doing discarding grievances and fighting, 2) the value of sharia education which contains values in the implementation of the pillars of Islam, 3) the value of moral education which contains Islamic personality values. Furthermore, Arsyad instills the values of Islamic religious education in students and the community using a rational development approach, clarification of values, cognitive, social behavior, instilling values, and using internal strategies and skills development strategies. Meanwhile, the methods for instilling values are example, oral bil (advice) and bil kitab (composing and writing). In Arsyad's view, the relevance of PAI values is both relevant and irrelevant to PAI material which continues to be enriched to answer current problems. The values of Islamic religious education in the thoughts of Sheikh Muhammad Arsyad al-Banjari contributed to education in his time in introducing and teaching the values of Islamic religious education.Key words: Syekh Arsyad Albanjari ; Islamic Education Concept